Behavioral Economics: An analysis of the socioeconomic impacts of digital media on the makeup market in the municipality of Capanema, Pará (Research, Society and Development, 2025)
This study aimed to analyse the main socio-economic impacts of digital media on the make-up market in the municipality of Capanema in the state of Pará. The study was conducted in Capanema, in the municipality of Capanema, northeast of Pará. A qualitative and quantitative approach was adopted, as well as bibliographic research to provide theoretical support for the study. Data collection was carried out using a semi-structured questionnaire containing 19 open and closed qualitative and quantitative questions. Primary data were thus obtained through questionnaires completed by 100 women in person and online between December 2024 and February 2025. The results revealed that the women participating in the research considered digital media to be the main source of information and not necessarily a tool for purchasing products. Furthermore, the study found that, although the frequency of makeup tends not to be recurrent among consumers, it is of substantial importance for the appreciation and elevation of self-esteem and feminine identity. Therefore, makeup tends to boost women's self-confidence in social situations, as feeling insecure about one's appearance can lead to personal dissatisfaction. Hence, it was concluded that, although reason is a predominant factor in the participants' purchasing decisions, emotions play a role in influencing their self-perception and product choices.